GERMANY’S (UN)SUCCESS IN IMPLEMENTING THE AMERICAN STRATEGY OF EXTENDED DETTERENCE AGAINST RUSSIA - Obrenović, Mile (National interest, 2024)
Considering the relationship between Germany and the United States through Lake’s theory of international hierarchies, it becomes apparent that Germany occupies a subordinate position within the security domain, which is at the very end of the hierarchical spectrum. At the core of this relationship is an "exchange": security for sovereignty, meaning that Germany delegates the responsibility for its security to the U.S. but is obligated to align its security policy with American policy, thereby losing part of its sovereignty.With the onset of the Russo-Ukrainian war in 2022, the U.S. opted for a strategy of extended deterrence against Russia, and Germany, as this hierarchical relationship suggests, aligned its defense policy with that of the U.S. and accepted its role in the American strategy of extended deterrence. Although Germany has played a significant role in U.S. efforts to deter Russia since the beginning of the war, the question arises as to whether the application of this strategy in the case of Germany has been successful. For a strategy to be considered successful, it must be both efficient and effective. The main hypothesis is that as time passes and the war progresses, Germany’s implementation of the strategy of extended deterrence is becoming evident as both ineffective and inefficient. To address the central research question, the paper is divided into three chapters. The first analyzes the relationship between Germany and the U.S. through Lake’s theory of international hierarchies, focusing on what this relationship means for Germany. The second examines why Germany initially believed in the success of the strategy of extended deterrence against Russia and how the U.S. contributed to that belief. Finally, the third chapter analyzes the effectiveness and efficiency of Germany’s application of the strategy of extended deterrence.